Structural Equation Modeling The Relationship between Self-compassion and Negative Emotional Responses to Failure: The Mediating Role of Cognetive Emotion Regulation - Mahmoud Mohebi; Hassan Gharayagh zandi; Mohammad Ali Besharat; Mahboubeh Ghayour Najafabadi (University of Tehran, 2021)
Recognition of important psychological factors in coping with difficulty is considered as an important factor in the development of positive interventions to achieve sports self-fulfillment. Self-sufficiency and cognitive regulation of emotion are important factors that are effective in coping with unpleasant events. In a difficult event such as failure in sports is not considered. Therefore The purpose of this study was to model the structural equation of relationship between self -compassion and emotional reactions to failure as mediated by cognitive emotion regulation among martial arts. A total of 286 athlete (191 men and 95 women; age: 20.98±3.30 years) from different disciplines of martial arts (taekwondo, karate, Judo and wushu) engaged in league championship participated in the study. Athlete completed self-report measures of self-compassion (SCS), negative affect (PANAS), and cognitive emotion regulation (CERQ). The proposed model was evaluated using structural equation model. Result revealed that self-compassion has direct and indirect effects on emotional reactions to failure. Furthermore, cognitive emotion regulation a partial negative mediator between the self-compassion and emotional reactions to failure. This study indicates that self-compassion is a relevant construct for understanding athletes'emotional responses to failure problems and cognitive emotion regulation strategies are involved as underlying mechanisms in this process. Therefore, it suggests paying attention to growth of self-compassion in martial arts and emphasizing on improving adaptive emotion regulation and reducing incompatible emotion regulation in order to recover better from failure and reduce its negative effects.